2022
DOI: 10.1007/s13311-022-01245-4
|View full text |Cite
|
Sign up to set email alerts
|

The Broad Range of Research in Alzheimer's Disease and Related Dementias

Abstract: Publisher's Note Springer Nature remains neutral with regard to jurisdictional claims in published maps and institutional affiliations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Additional risk factors include having one or more apolipoprotein gene E4 alleles (APOE4), having a family history of AD, having inadequate occupational and educational skills, having cardiovascular risk factors, and having experienced moderate to severe brain injuries [ 57 ]. According to the cholinergic hypothesis, the gradual loss of limbic and neocortical cholinergic innervation in AD is responsible for the decrease in memory, learning, attention, and other higher brain processes [ 58 ]. Furthermore, neurofibrillary degeneration in the basal forebrain is most likely the major source of cholinergic cell malfunction and mortality in this area, resulting in broad presynaptic cholinergic denervation.…”
Section: Alzheimer’s Diseasementioning
confidence: 99%
“…Additional risk factors include having one or more apolipoprotein gene E4 alleles (APOE4), having a family history of AD, having inadequate occupational and educational skills, having cardiovascular risk factors, and having experienced moderate to severe brain injuries [ 57 ]. According to the cholinergic hypothesis, the gradual loss of limbic and neocortical cholinergic innervation in AD is responsible for the decrease in memory, learning, attention, and other higher brain processes [ 58 ]. Furthermore, neurofibrillary degeneration in the basal forebrain is most likely the major source of cholinergic cell malfunction and mortality in this area, resulting in broad presynaptic cholinergic denervation.…”
Section: Alzheimer’s Diseasementioning
confidence: 99%
“…1−5 Alzheimer's disease (AD) and Parkinsonian syndromes are the most representative neurodegenerative disorders that are broadly spreading over the world. 6 Cortical basal degeneration (CBD) and primary supranuclear palsy (PSP) represent atypical forms of Parkinsonian syndromes and are considered as primary tauopathies with an underlying brain aggregation of tau proteins. 7,8 It has been reported that most of these abnormal protein aggregates are present in the brain much in advance of the appearance of dementia symptoms.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Proteinopathies is a broad umbrella term used to represent neurodegenerative disorders that are characterized by different target proteins and featured by the formation of abnormal protein aggregates in the brain, such as amyloid-β (Aβ), tau, and α-synuclein. Alzheimer’s disease (AD) and Parkinsonian syndromes are the most representative neurodegenerative disorders that are broadly spreading over the world . Cortical basal degeneration (CBD) and primary supranuclear palsy (PSP) represent atypical forms of Parkinsonian syndromes and are considered as primary tauopathies with an underlying brain aggregation of tau proteins. , It has been reported that most of these abnormal protein aggregates are present in the brain much in advance of the appearance of dementia symptoms .…”
Section: Introductionmentioning
confidence: 99%